2020
DOI: 10.1111/dth.13998
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of assessment of serum zinc levels in patients with vitiligo: A patient controlled prospective study

Abstract: Vitiligo is an autoimmune disease characterized by patches of depigmentation. Zinc is an antiapoptotic molecule that exhibits antioxidant properties. The study aimed to investigate the serum levels of zinc in vitiligo patients compared to healthy controls and to whether exists a correlation between disease severity and serum levels of zinc. Fifty patients with vitilgo (group A) and 50 age and sex matched healthy controls (group B) were recruited and serum zinc level was measured using atomic absorption spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
9
0
3
Order By: Relevance
“…A case-control study by Basha MA et al 18 in 2015 which involved 60 patients and 60 controls observed no significant correlation of serum zinc with age of onset (p value=0.04) or disease duration (p value=0.65). Similar observations were made by Zaki et al 19 2020. In contrast, Mirnezami M et al 20 in 2018 found a significantly lower serum zinc level associated with longer vitiligo duration.…”
Section: Discussionsupporting
confidence: 90%
“…A case-control study by Basha MA et al 18 in 2015 which involved 60 patients and 60 controls observed no significant correlation of serum zinc with age of onset (p value=0.04) or disease duration (p value=0.65). Similar observations were made by Zaki et al 19 2020. In contrast, Mirnezami M et al 20 in 2018 found a significantly lower serum zinc level associated with longer vitiligo duration.…”
Section: Discussionsupporting
confidence: 90%
“…Most of studies revealed low levels while others showed normal or even high level, this may be explained by some nutritional factors as excessive supplement therapy, differences in diet quality, zinc concentration in soil, consumption of large amount of phytate, in addition to an important factor which is the inequality in cut-off point of normal zinc levels [21]. Our study considered 46 ug/dl as the low limit of normal zinc level, while other studies revealed a higher reference level, for example Zaki et al [21] considered the low limit of normal zinc level was 65 ug/dl. Also, Rostami mogaddam et al [22] considered the low limit of normal zinc level 70 ug/dl and Zn deficiency was described as a serum Zn level <70ug/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is a primary, localized, or generalized depigmentation of the skin and mucosa. Several studies have found that zinc levels in patients with vitiligo are lower than in controls ( 105 108 ). There are very few studies on the role of zinc in therapy, and only Yahoobi et al reported a clinical trial comparing the therapeutic effect of topical corticosteroids to a combination of oral zinc sulfate and topical corticosteroids.…”
Section: Pigmental Diseasesmentioning
confidence: 99%